Increased Color Brightness with the Addition of Astaxanthin in Koi Fish (Cyprinus Rubrofuscus) Feed - Suryati Panjaitan, Amyda (Journal of World Science, 2023)
Introduction: This research was conducted experimentally from May to July 2021 at the Teaching Factory Cultivation Laboratory (TEFA) of the Jakarta Fisheries Business Specialist Polytechnic. This study aims to determine the effect of astaxanthin feeding on increasing color, survival and growth of koi fish. Method: The research method used is quantitative. The design used was a completely randomized design (CRD) with four treatment levels and three replications. Analysis of variance used was analysis of variance (ANOVA. Results: The results showed that the addition of astaxanthin to feed had a significant effect on changes in the color quality of koi fish. The best result was the addition of astaxanthin 125 mg/kg feed (20.29 ± average weight measurement results) (ABW) at the end of the study obtained the highest value in treatment A (control) of 10.37 g. The results of the average weight measurement (ABW) at the end of the study obtained the highest value in treatment A (control) of 10.37 g, Specific Growth Rate (SGR) was the highest in treatment A (control) of 12.00%, the best Feed Conversion Ratio (FCR) was in the treatment with the addition of 100 mg astaxanthin 1.12. Conclusion: The use of astaxanthin in koi fish feed can increase the selling value of koi fish in the market because of the bright color is one of the important criteria in assessing the quality of koi fish. Koi fish farmers can consider adding astaxanthin and need to pay attention to the right dosage.